Oral Tradition Ende Padang in the Angkola Ethnic - Risky Pratama Siregar (Tradition and Modernity of Humanity, 2026)
The Angkola ethnic community is part of an oral tradition containing cultural, social, and educational values. Ende Padang is one example of an oral tradition inherited by the Angkola community through a process of cultural transmission from generation to generation. This study adopted a descriptive qualitative approach based on the theory of oral tradition. Data were obtained through a literature review of various references related to the oral tradition of the Angkola community. The findings of this study indicate that Ende Padang serves as a means of entertainment, a tool for conveying advice, strengthening cultural identity, and a medium for transferring social values among the Angkola community. From the perspective of oral tradition, Ende Padang is a form of cultural expression that has a structure, meaning, and social function that are very important for the life of the community that supports it. Efforts to preserve Ende Padang are becoming increasingly urgent amidst the shift in modernization that threatens the sustainability of local oral traditions.